Zines as Reflective Evaluation Within Interdisciplinary Learning Programmes - Brown, Autumn; Hurley, Mairéad; Perry, Sophie; Roche, Joseph (Frontiers in Education, 2021)
This paper presents a unique method for documenting and reflecting learning in interdisciplinary science learning settings, which prioritises the perspectives of marginalised learners and which may be used across cultural contexts. Short for “magazine” or “fanzine”, zines are small DIY booklets which can contain poetry, narrative, drawings, comics, collage and more. Often associated with radical or alternative cultures, they can become a kind of self-made soapbox for the creator, a material artefact that, by its very deconstructed and deconstructing nature, encourages a personalised remixing of ideas. Within this paper, we examine the practical and pedagogical positioning of zines within a STEAM (Science, Technology, Engineering, Arts, and Mathematics) context. As both a visual and text-based artefact, a zine is uniquely capable of capturing broad responses to diverse learning experiences which blur disciplinary boundaries and offers an inclusive and firmly emancipatory approach to reflective practice.